Rethinking structural competency: Continuing education in mental health and practices of territorialisation in Brazil - Francisco Ortega; Manuela Rodrigues Müller (Taylor & Francis Group, 2023)
Brazilian mental health focuses on the social determination model within mental health policies and interventions to address mental and social suffering as resulting from social exclusion and structural violence. Structural concerns focused on class stratification and socioeconomic inequalities overweight cultural ones in Brazilian mental health. In this article we examine, first the role of culture and interculturality in mental health practices and mental health guidelines for health professionals continuing training in Brazil. Second, we explore interviews with health professionals around Continuing Education in Health provided by mental health collaborative care initiatives within primary health care as illustration of a local practice of structural competency in mental health. Finally, we examine the central role played by the practices of territorialisation in shaping health care training and care interventions. The focus on the territory can promote critical apprehensions of the intercultural and structural factors that shape health practices, enrich health professional education oriented towards the basic tenets of social medicine and provide global discussions around structural competency with innovative ways of thinking about health education, health care and spatiality. We believe that our results may be useful for comparing structural competency training initiatives in global health.